Shear strength parameters of unsaturated residual soils - Bujang B.K. Huat,; Faisal Hj. Ali,; Affendi Abdullah,; Saravanan Mariappan,; Soenita Hashim, (2005)
The shear strength envelope for unsaturated soil requires that three shear strength parameters be defined namely, c', ø' and øb. These parameters can be measured in the laboratory. The c' and ø' parameters can be measured using standard laboratory equipment on saturated soil specimen. However conventional triaxial and direct shear equipment require modifications prior to their use, i.e. for suction induced tests on unsaturated soils to measure the øb (i.e. the change in shear strength with respect to suction). This paper describes the modification made to the standard laboratory triaxial and shear box and outline the test performed for measuring the shear strength parameters of unsaturated residual soils. The value cohesion, c' is found to increase with increase in the matric suction. For a given level of matric suction, the cohesion appear to increase with increase in the soil weathering grade, i.e as the soils/rocks becomes more weathered. The angle of friction, ø' decreases with increase in the soils weathering grade, but the angle of friction or change in shear strength with change in suction, øb , increases when the soil becomes more weathered. The values of øb are generally lower than ø'